Increased depth to the water table during river drying decreases the resilience of Gammarus pulex and alters ecosystem function. Issue 7 (15th February 2016) - Vander Vorste, Ross; Mermillod‐Blondin, F.; Hervant, F.; Mons, R.; Forcellini, M.; Datry, T.
Abstract: River drying has drastic immediate effects on benthic invertebrates, but their high resilience reduces long‐term effects on biodiversity and ecosystem functions (e.g. leaf litter decomposition). The hyporheic zone (saturated sediments below the riverbed) can be a refuge for invertebrates in dry rivers and a primary source of colonists supporting population resilience following flow resumption. However, factors such as the depth to the water table below the riverbed, which could determine the quality of the hyporheic refuge, are not well understood. We explored how depth to the water table (control, −5 cm, −30 cm and completely dry) during a 1‐week drying event affected the survival and return to the substrate surface (%RTS) of Gammarus pulex (Crustacea : Amphipoda) using laboratory mesocosms. We measured litter decomposition and Gammarus energy stores to examine effects on ecosystem function and energetic costs for organisms crawling deeper into the hyporheic zone. Two populations, collected from intermittent and perennial rivers, were used to evaluate inter‐population variability in response to drying. Survival and %RTS were reduced by ≤39% and 52%, respectively, in the −30 cm and dry treatments, and this had consequences for decomposition (≤46% reduction). Differences between populations in %RTS were high across treatments but did not generally affect survival and decomposition. Our results suggest that increases in depth to the water table during river drying, which often result from longer drying duration and water abstraction, could reduce invertebrate resilience and litter decomposition by diminishing the role of the hyporheic zone as a source of colonists. Copyright © 2015 John Wiley & Sons, Ltd.